The local food environment and its association with obesity among low-income women across the urban-rural continuum - Ford, Paula Brigid (Kansas State University, 2009)
The prevalence of obesity within the U.S. has risen dramatically in the past thirty years. Recent changes in food and physical activity environments may contribute to increased obesity prevalence, suggesting that disparities in these environments may be linked to the increased risk of obesity observed in low-income, and racial/ethnic minority women. This dissertation characterizes the local food environment experienced by low-income women who participate in the Special Supplemental Nutrition Program for Women, Infants, and Children (WIC) in Kansas, evaluates whether characteristics of the local food environment contribute to obesity risk, and examines how these relationships vary across the urban-rural continuum. Chapter One reviews the relevant literature examining the association between obesity and local food environments, and identifies three testable hypotheses that serve as the framework for later chapters. Chapter Two characterizes the local food environment and examines geographic, racial, ethnic, and socioeconomic disparities in the availability of small grocery stores and supermarkets. Chapter Three examines the association between store availability and obesity risk at an individual level among participants in the WIC Program, while Chapter Four utilizes multi-level modeling to examine the relationships between tract deprivation, tract store availability and body mass index (BMI). Significant geographic disparities were observed in the availability of small grocery and supermarkets. Racial and ethnic disparities observed within tracts were not observed when examining store availability in a 1-mile radius around the residence of WIC mothers. The majority of women participating in the WIC program resided within a 1-mile radius of a small grocery store, and micropolitan and metropolitan WIC mothers had a multiplicity of food stores available within a 3-mile radius of residence. Food store availability was associated with increased obesity risk only in micropolitan areas. The availability of food stores did not mediate the association between tract deprivation and BMI, which varied across the urban-rural continuum. Overall, these results suggest that the relationship between local food environments and eating behaviors is complex, that limited store availability does not contribute to increased obesity risk in vulnerable populations, and that the association between local food environments and obesity risk varies across the urban-rural continuum.
Keywords: Obesity; Food environment; Food deserts; Supermarket availability; Food access; Neighborhood effects; Health Sciences, Nutrition (0570); Health Sciences, Public Health (0573)